2017
DOI: 10.1001/jama.2017.9479
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cerebral Embolic Protection Devices on CNS Infarction in Surgical Aortic Valve Replacement

Abstract: IMPORTANCE Stroke is a major complication of surgical aortic valve replacement. OBJECTIVE To determine the effectiveness and safety of cerebral embolic protection devices in reducing ischemic central nervous system injury during surgical aortic valve replacement DESIGN, SETTING and PARTICIPANTS A parallel-group trial conducted in 18 North American centers, randomizing patients with calcific aortic stenosis undergoing surgical aortic valve replacement between March 2015 and July 2016. INTERVENTIONS Use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 34 publications
(86 reference statements)
2
46
0
Order By: Relevance
“…More recently published data showed the opposite results with more favorable clinical outcomes after stroke following TAVR (Table ) . On the other hand, the evaluation of embolic protection during SAVR have shown a substantial number of debris captured in most patients with embolic protection device, without significant reduction in silent or clinical stroke at either 7 or 30 days . As many as 625 patients have been randomized across several clinical trials evaluating cerebral protection during TAVR .…”
Section: Discussionmentioning
confidence: 99%
“…More recently published data showed the opposite results with more favorable clinical outcomes after stroke following TAVR (Table ) . On the other hand, the evaluation of embolic protection during SAVR have shown a substantial number of debris captured in most patients with embolic protection device, without significant reduction in silent or clinical stroke at either 7 or 30 days . As many as 625 patients have been randomized across several clinical trials evaluating cerebral protection during TAVR .…”
Section: Discussionmentioning
confidence: 99%
“…Identifier: NCT02389894), the use of cerebral EPD failed to demonstrate a decreased number of clinical or radiologic strokes after isolated surgical aortic valve replacement or combined aortic valve replacement and coronary artery bypass graft surgery. 6 The study demonstrated that although EDP captured embolic material in 74% to 99% of the patients, only 5% of patients have clinically apparent strokes even with a rigorous stoke adjudication process. Meanwhile, at least 70% of the patients had new ''bright lesions'' on dw-MRI, and their incidence was not different between the study and control groups.…”
mentioning
confidence: 92%
“…Yet, these ''bright lesions'' on dw-MRI are unlikely to make anybody any brighter because their volume is correlated with worse neuropsychologic and cognitive outcomes. 6,7,9 Do you want them in your brain? I don't.…”
mentioning
confidence: 99%
“…The trial was stopped early due to an interim analysis for futility. Though the devices captured debris in most patients, freedom from clinical or radiographic CNS infarction, the primary endpoint, was not observed 68. MoCA score of 26 as the threshold for impairment, impaired patients had higher total median lesion volumes (163.18 cm 3 ) compared to unimpaired patients (130.05 cm 3 ) 15.…”
mentioning
confidence: 98%